Human genetic determinants of tamoxifen metabolism - Koh, Everett Chier Wei (Nanyang Technological University, 2021)
Germline DNA variants have been found to have an impact on a diverse range of human traits, including the ability to metabolise drugs. In this study, we analysed the association between human genetic variants and serum tamoxifen metabolite levels at steady state in breast cancer patients from Singapore, Germany, and Lebanon. Our study found a strong association between a common genetic marker (rs5751245) on Chromosome 22 with log-transformed serum endoxifen levels (p=1.2 ×10^(-28)). Because CYP2D6 is a well-known metaboliser of endoxifen, we also conducted genome-wide association for CYP2D6 expression quantitative trait loci (eQTL). We found a common genetic marker (rs2413670) to be strongly associated with both endoxifen (p_endo=1.2 ×10^(-23)) and CYP2D6 eQTL (p_(CYP2D6_eQTL )=2.9 ×10^(-14)). In combination, rs5751245 and rs2413670 explain up to 30% of the variance observed in steady-state serum endoxifen levels. Our findings further contribute to our understanding of the genetic architecture of endoxifen metabolism, with the potential for translation into better outcomes for estrogen-receptor positive breast cancer patients.